(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Biobanks, as specialized facilities for the collection and storage of biological samples and for the processing of personal data, represent a powerful tool for the discovery of new treatments in medicine, as well as in the identification of offenders in forensic science. Nevertheless, their use raises important ethical and legal issues, as their activity affects the fundamental rights of the individual, such as self-determination, confidentiality and protection of personal data. From the legal point of view, it is therefore necessary to find a balance between the rights of the individual and the collective interests in biomedical research and public security.